2020
DOI: 10.1038/s12276-020-0375-3
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids in cancer

Abstract: Over 90 years ago, Otto Warburg's seminal discovery of aerobic glycolysis established metabolic reprogramming as one of the first distinguishing characteristics of cancer 1. The field of cancer metabolism subsequently revealed additional metabolic alterations in cancer by focusing on central carbon metabolism, including the citric acid cycle and pentose phosphate pathway. Recent reports have, however, uncovered substantial non-carbon metabolism contributions to cancer cell viability and growth. Amino acids, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
429
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 522 publications
(488 citation statements)
references
References 173 publications
(245 reference statements)
4
429
0
7
Order By: Relevance
“…The influential roles of methionine in cancer cell growth has been well-documented [ 96 , 97 , 98 , 99 ]. Methionine is involved in several critical activities in cancer cells, such as nucleotide biosynthesis via the one-carbon metabolism pathway [ 100 , 101 , 102 ] and protein synthesis [ 103 ]. Methionine is also a precursor metabolite of S-adenosylmethionine, a co-substrate involved in methyl group donation, for cellular processes such as epigenetic control and protein methylation [ 100 , 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The influential roles of methionine in cancer cell growth has been well-documented [ 96 , 97 , 98 , 99 ]. Methionine is involved in several critical activities in cancer cells, such as nucleotide biosynthesis via the one-carbon metabolism pathway [ 100 , 101 , 102 ] and protein synthesis [ 103 ]. Methionine is also a precursor metabolite of S-adenosylmethionine, a co-substrate involved in methyl group donation, for cellular processes such as epigenetic control and protein methylation [ 100 , 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methionine is involved in several critical activities in cancer cells, such as nucleotide biosynthesis via the one-carbon metabolism pathway [ 100 , 101 , 102 ] and protein synthesis [ 103 ]. Methionine is also a precursor metabolite of S-adenosylmethionine, a co-substrate involved in methyl group donation, for cellular processes such as epigenetic control and protein methylation [ 100 , 104 , 105 ]. Previous reviews have identified that the DNA methylation patterns in lung cancer were altered, where genome-wide hypomethylation, and hypermethylation of the promoter regions of several tumor suppressor genes, such as DAPK , RASSF1A and RARβ , were commonly observed [ 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could explain the activated OxPhos metabolism that we have found in the RT4 cells, which determines a higher consumption of glutamine, BCAAs and serine. Both glutamine and BCAAs can act as anaplerosis metabolites driving the TCA cycle through the generation of alpha-ketoglutarate [23] and acetyl-CoA, respectively [24]. Likewise, the increased uptake and catabolism of serine, with higher excretion of formate and glycine, is related to a higher mitochondrial activity.…”
Section: Discussionmentioning
confidence: 99%